Ritul Poancino Buku pada Masyarakat di Desa Marobo Kecamatan Marobo Kabupaten Muna - farida; Nurtikawati Nurtikawati; La Ode Marhini (LISANI: Jurnal Kelisanan, Sastra, dan Budaya, 2023)
This study aims to describe the process of carrying out the Poancino Buku ritual for the community in Marobo Village, Marobo District, Muna Regency and describe the symbolic meaning contained in the Poancino Buku ritual. as well as describing the prohibition of the Poancino Buku ritual for the community in Marobo Village, Marobo District, Muna Regency. The method used in this research is descriptive qualitative. Primary data was obtained through in-depth interviews, namely to those who have been found using purposive sampling techniques. As well as direct observation in the field. Secondary data was obtained from data collection through documents and literature related to the research topic. The data collected was then analyzed by means of data collection, data reduction, data presentation and drawing conclusions. The results of this study are: (1) the process of carrying out the Poancino Buku ritual includes: the notification stage to the village shaman, the family gathering stage, the preparation stage, namely gathering materials and tools to be used in the Poancino Buku ritual. the implementation stage is the reading of prayers in the yard guided by a village shaman. And the final stage / closing. (2) the symbolic meaning of the Poancino ritual The book has meaning in the offerings provided including hono lapi (lapi leaves) as a symbol of the Koran, kahoho (sirik leaves), kowala (janur) & ma'keno me'a (areca nut) as a symbol of connecting with God Tallah. Oci (rice), unteli (eggs) & kenta katamba (katamba fish) have symbolic meanings as carriers of sustenance for certain people. incense (incense) as a symbol of notification to Allah SWT, that the community is carrying out the Poancino Buku ritual. (3) the prohibition of the Poancino Buku ritual, namely that for four days and four nights the people who carry out the ritual may not give goods or objects to other people because for four days and four nights their fortune is still in the diombo stage.